Identifikasi Staphylococcus aureus pada Daging Ayam yang Dijual di Pasar Besar Kota Palangka Raya - Rahmawati Rahmawati; Eva Apriliana; Agus Agus (Borneo Journal of Medical Laboratory Technology, 2018)
Staphylococcus aureus can be a cause of food poisoning in humans. This type of bacteria can produce enterotoxins that cause contaminated food and poisoning in humans. The toxin produced is resistant in high temperatures, although the bacteria die by heating but the resulting toxin will not be damaged and can still change despite freezing or freezing. Staphylococcus aureus is commonly found in high-protein foods such as egg and chicken products. The purpose of this study was to investigate the contamination of Staphylococcus aureus bacteria in chicken meat sold in Pasar Besar Kota Palangka Raya in 2018. The examination using MSA media (Mannitol Salt Agar) because MSA media is different selective media to differentiate Staphylococcus aureus with Staphylococcus epidermidis. The results of analysis of chicken meat in Pasar Besar Kota Palangka Raya 20% positive contaminated Staphylococcus aureus bacteria in the first-day sample. In the second day, the sample found 13.3% positive contaminated Staphylococcus aureus bacteria.